Economics Beyond Markets: Choice Experiments In Developing Countries - Birol, Ekin (2010)
June 21, 2010 IFPRI Policy Seminar Washington, DC Economics Beyond Markets: Choice Experiments In Developing Countries Jeff Bennett Ekin Birol Derek Byerlee